Towards development of a tele‐mentoring framework for minimally invasive surgeries. Issue 5 (18th July 2021) - Shabir, Dehlela; Abdurahiman, Nihal; Padhan, Jhasketan; Trinh, May; Balakrishnan, Shidin; Kurer, Mohamed; Ali, Omar; Al‐Ansari, Abdulla; Yaacoub, Elias; Deng, Zhigang; Erbad, Aiman; Mohammed, Amr; et al.
Abstract: Background: Tele‐mentoring facilitates the transfer of surgical knowledge. The objective of this work is to develop a tele‐mentoring framework that enables a specialist surgeon to mentor an operating surgeon by transferring information in a form of surgical instruments' motion required during a minimally invasive surgery. Method: A tele‐mentoring framework is developed to transfer video stream of the surgical field, poses of the scope and port placement from the operating room to a remote location. From the remote location, the motion of virtual surgical instruments augmented onto the surgical field is sent to the operating room. Results: The proposed framework is suitable to be integrated with laparoscopic as well as robotic surgeries. It takes on average 1.56 s to send information from the operating room to the remote location and 0.089 s for vice versa over a local area network. Conclusions: The work demonstrates a tele‐mentoring framework that enables a specialist surgeon to mentor an operating surgeon during a minimally invasive surgery.